Smartphone-Based Short Film Making Training Using CapCut to Enhance Community Digital Creativity - Nurcahyawati, Enny; Wijayanto, Catur Sunu; Nugraha, Renanda Adhi (Neolectura, 2026)
The rapid development of digital technology has significantly transformed the way people produce and distribute multimedia-based information. Smartphones, as accessible digital devices, enable individuals to independently create audiovisual content; however, the community’s ability to utilize such technology creatively remains relatively limited. This community service program aimed to improve digital literacy and enhance participants’ skills in producing smartphone-based short films using the CapCut application. The program employed a participatory training approach consisting of preparation, implementation, hands-on practice, mentoring, and evaluation stages. The activity involved 12 participants from Universitas Indraprasta PGRI. The training materials included the basic concepts of short film production, smartphone cinematography techniques, storyline development, and video editing practices using CapCut. Evaluation was conducted through observation, video production practice, and discussions regarding participants’ final projects. The results demonstrated an improvement in participants’ understanding of short film production processes and video editing techniques after the training. Most participants were able to produce simple short films with more structured storylines and creative visual effects. Furthermore, participants’ video editing skills increased by approximately 40% based on practical assessment results during the training sessions. The program also positively contributed to enhancing participants’ creativity, visual communication skills, and self-confidence in utilizing digital media as a means of expression and communication in the digital era.